PERAN KELUARGA DALAM PENDIDIKAN AKHLAK ANAK (STUDI KASUS ANAK USIA 6-12 TAHUN DI KELURAHAN WONOKOYO RT 03 RW 02 MALANG) - Yuni Ariska; Mohammad Afifulloh; Lia Nur Atiqoh Bela Dina (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
The family is the main place for education in shaping the character, personality and character of the child. Good or bad behavior of a child can be seen from how his family, because the family is seen as a benchmark of behavior of each individual. Therefore, education obtained by children in the family which will affect the subsequent education. The very influential family component is parents, these parents play an important role and are obliged to educate and guide their children in everything about life, especially regarding moral education and religion. The focus of the problem in this study is how the role of the family in the moral education of children aged 6-12 years. The purpose of this study is to describe and analyze the role of families in the moral education of children aged 6-12 years. This study uses a qualitative research approach, type of case study research. Data collection procedures are carried out using the method of observation, interviews, and documentation. The results of the study showed that the role of the family in the moral education of children aged 6-12 years in Wonokoyo Village Rt 03 Rw 02 is in three ways: forming child worship activities, instilling adab to children, and instilling an attitude of honesty to children.